Structure and Phase Behavior of Interpolyelectrolyte Complexes of PDADMAC and Hydrophobically Modified PAA (HM‐PAA). Issue 1 (27th November 2022) - Kuzminskaya, Olga; Riemer, Sven; Dalgliesh, Robert; Almásy, László; Hoffmann, Ingo; Gradzielski, Michael
Abstract: By combining oppositely charged polydiallyldimethylammonium chloride (PDADMAC) and sodium polyacrylate (NaPA), interpolyelectrolyte complexes (IPECs) can be formed in aqueous solution. Such IPECs are studied for rather short NaPA and under variation of the Mw of PDADMAC. The focus is on elucidating the effect of having a hydrophobic modification of the NaPA, which is introduced by having 10 mol% of the monomeric units substituted by ones carrying a dodecyl alkyl chain. This modification renders the complexes more hydrophobic, which is seen in the fact that precipitation of the complexes occurs at a lower mixing ratio and the biphasic region is also wider. The structures of the soluble IPECs are studied by a combination of light and neutron scattering (SANS). It is observed that the complexes formed possess typical radii of gyration of ≈30–40 nm, which become somewhat smaller with increasing length of the PDADMAC chain. The SANS data can be described well with the Beaucage model for complexes, where locally small hydrophobic domains of cylindrical shape are formed, whose persistence length decreases with increasing content of NaPA in the complexes. In contrast no such structures are seen for NaPA without the hydrophobic modification. The cylindrical domains are then arranged within larger‐sized clusters of 30–40 nm, which become more compact with reduced length of the PDAMAC chains. The structure of the IPECs is largely determined by the presence of the hydrophobic modification of the NaPA and is further controlled by the length of the hydrophobic modification. Such IPECs of controlled structure, relatively small size, and containing hydrophobic domains are potentially interesting as delivery systems due to having domains of variable polarity. Abstract : Interpolyelectrolyte complexes (IPECs) of PDADMAC are formed with normal and hydrophobically modified PAA. This modification leads to the formation of much larger complexes with an internal substructuring. SANS yields a detailed structural description of the aggregates, which on a nm‐level are cylindrical. Hydrophobic polyelectrolyte modification is therefore an elegant way to control structure and properties of IPECs.